2023
DOI: 10.3390/brainsci13040621
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence Reveals the Asymmetric Transfer from the Right to Left Hemisphere as Key to Reading Proficiency

Abstract: The present investigation aimed to explore the interhemispheric interactions that contribute to changes in reading proficiency by examining the processing of visual word recognition in relation to word familiarity. A lexical decision task was administered to 25 participants, and their electrophysiological activity was recorded. A behavioral analysis showed the faster and more accurate processing of highly familiar words compared to less familiar ones. An event-related potential analysis uncovered an asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Additionally, due to the greater availability of relevant lexical information in the left hemisphere compared to the right, the involvement of the right hemisphere in foveal word processing may necessitate more resources than relying on the left hemisphere's strategy. In this regard, Kim et al (2023) offer electrophysiological evidence supporting superior facilitation from the right to the left hemisphere during more familiar word recognition at foveal vision, which may lead to left-lateralization for efficient foveal word processing. Furthermore, parafoveal studies have shown that word processing operates cooperatively between the two hemispheres to achieve efficient processing by modulating word familiarity (Kim et al, 2022) and semantic information of words (Perrone-Bertolotti et al, 2013) with the significant RVFA.…”
Section: Why Task Demand Matters In Lexical Decision and Its Relation...mentioning
confidence: 89%
“…Additionally, due to the greater availability of relevant lexical information in the left hemisphere compared to the right, the involvement of the right hemisphere in foveal word processing may necessitate more resources than relying on the left hemisphere's strategy. In this regard, Kim et al (2023) offer electrophysiological evidence supporting superior facilitation from the right to the left hemisphere during more familiar word recognition at foveal vision, which may lead to left-lateralization for efficient foveal word processing. Furthermore, parafoveal studies have shown that word processing operates cooperatively between the two hemispheres to achieve efficient processing by modulating word familiarity (Kim et al, 2022) and semantic information of words (Perrone-Bertolotti et al, 2013) with the significant RVFA.…”
Section: Why Task Demand Matters In Lexical Decision and Its Relation...mentioning
confidence: 89%